Research progress on GlnR-mediated regulation in Actinomycetes - Gao, Bo; Li, Guoqiang; Gu, Dayong; Wang, Jin (Frontiers in Microbiology, 2023)
This review constitutes a summary of current knowledge on GlnR, a global regulator, that assumes a critical function in the regulation of nitrogen metabolism of Actinomycetes. In cross-regulation with other regulators, GlnR was also shown to play a role in the regulation of carbon and phosphate metabolisms as well as of secondary metabolism. A description of the structure of the GlnR protein and of its binding sites in various genes promoters regions is also provided. This review thus provides a global understanding of the critical function played by GlnR in the regulation of primary and secondary metabolism in Actinomycetes.